Baba bakery cakes - Sy-Iarizzad, Raja Nur Qurratu Ain; Musa, Faziera Hanis; Kama-Rulasri, Nur Hasya Rushaida; Abu Samah, Fatin Nurjiha; Azman, Diana Haziqah Izzati (2021)
Baba Bakery is a business that can be categorized as Small Medium Enterprise (SME) which provide food service to customer. The business is based on partnership where it consists of five (5) members which hold an important position in the business such as general manager and pastry chef. The business capital is amount RM 390,661 where the total contribution is RM 282,661 and from Bank Islam’s loan is RM 108,000. Baba bakery is located at Seksyen 7, Shah Alam which is near to UiTM Shah Alam. We choose the location because it is strategic base on our research. As we know that Seksyen 7 Shah Alam is one of a hotspot places to start up a shop. We believe by choosing a right location can affect our business. Baba Bakery are specialized in baking and decorating cakes for any occasions. Baba Bakery aim to offer its product at a competitive price to meet demand of the low to higher income local market area residents. Baba Bakery baked fresh cakes daily. We sale in slice and whole cake for customer. In Baba Bakery we also provide deco-rating cake upon customer request. Customer can custom the flavour of the cake and the decoration of the cake. In our bakery we also provide delivery services to customer which is will make customer easy to pick up cake without needed going to our bakery. With loan given as a support from Bank Islam we hoping to make Baba Bakery can be able to achieve outstanding demand from customer. Our business is expected commence on 1st January 2021 and our vision is to make our business as well know and established. We target to open more brunches in Malaysia and expend Baba Bak-ery in Asian country. We believe in “To build a successful business, you must start small and big dream”.